Food wastes management: practice of composting process at the IIUM Kuantan Campus - Abu Samah, Mohd Armi; Yunus, Kamaruzzaman; Wan Kamal, Wan Mohd. Hilmi; Mohd. Hussain, Mohd. Ramzi; Hassan Basri, Raszera (Taylor & Francis Group, 2021)
Malaysian population has been increasing at a rate of 2.4% per year or about 600,000 per year since 1994. With this population growth, the municipal solid waste (MSW) generation also rises, which makes municipal solid waste management important. Changes in municipal solid waste generation rates are mostly caused by socioeconomic characteristics of a population and facilities, which are provided by the various departments. Malaysian solid waste contains a very high amount of organic waste and consequently has high moisture content and a bulk density above 200kg/m3. Nowadays, the only way used for the managing and discarding of MSW in Malaysia is landfilling. The disposal of wastes through landfilling is becoming more complicated because vacant landfill sites are filling up at a very rapid rate. This article aims to shed light on the origins of food waste, both pre-consumer and post-consumer. Secondly, the impacts and challenges of cutting down on food waste produced in IIUM Kuantan Campus will also are discussed. 208On top of that, this article will propose a new system which is by using a composting machine to manage food waste with proper management and cleans.